2007
DOI: 10.1080/01448765.2007.10823210
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Mobilisation and Immobilisation Vary in the Root Environment of Different Barley Genotypes with Different Phosphate Sources

Abstract: A method was developed to estimate root efficiency of barley (Hordeum vulgare L.) in making available phosphorus (P) from vatious unlabelled, spatingly-soluble compounds containing P. The post-treatment method is based on axenic germination on a P-free medium, removing the seedling from the medium and incubating the P substance to be tested in situ in the medium, followed by soluble P determination. Seven lines oflandrace barley were tested with 8 day old seedlings. CaHPO, was found to be dissolved by five of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…In the case of apatite as fertilizer, including Siilinjärvi Apatite, the field trials with annual barley in organic farming (Seuri et al 2001) corroborate the finding that P of apatite is unavailable or poor available to barley. This was confirmed with 7 other barley genotypes with an in vitro method (Ahokas et al 2007). In soil, the tested compounds would be subjected to biological leaching.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…In the case of apatite as fertilizer, including Siilinjärvi Apatite, the field trials with annual barley in organic farming (Seuri et al 2001) corroborate the finding that P of apatite is unavailable or poor available to barley. This was confirmed with 7 other barley genotypes with an in vitro method (Ahokas et al 2007). In soil, the tested compounds would be subjected to biological leaching.…”
Section: Discussionsupporting
confidence: 55%
“…The six pea genotypes did not differ in their ability to solubilise phosphate from CaP significantly (Table 3, 4) even though Ahokas et al (2007) found differences among the barley genotypes. Iron phosphate is one of the major deposited forms of P in peat soils in Finland (Valmari 1970; Nieminen and Jarva 1996) and in field soils that have been fertilized (Hartikainen 1989) with a surplus of P since the 1940s (Saarela et al 2003).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In recent years, considerable research has shown that variation in root system architecture plays a key role in crop nutrient efficiency (Lynch ). Correspondingly, root architecture also can be significantly influenced by nutrient availability, heterogeneity of nutrient supply and symbiotic microorganisms (Williamson et al ; Linkohr et al ; He et al ; Yano and Kume ; Walch‐Liu et al ; Ahokas et al ; Wang et al ; Wu et al ).…”
Section: Introductionmentioning
confidence: 99%